Cohomologies of deformations of solvmanifolds and closedness of some properties - Angella, Daniele; Kasuya , Hisashi (North-Western European Journal of Mathematics, 2023)
We provide further techniques to study the Dolbeault and Bott-Chern cohomologies of deformations of solvmanifolds by means of finite-dimensional complexes. By these techniques, we can compute the Dolbeault and Bott-Chern cohomologies of some complex solvmanifolds, and we also get explicit examples, showing in particular that either the \(\)-Lemma or the property that the Hodge and Frölicher spectral sequence degenerates at the first level are not closed under deformations.